Smart phone application for real-time optimization of rower movements - Kastner, M.; Sever, A.; Hager, C.; Sommer, T.; Schmidt, S. (Procedia Engineering, 2010)
We present a smart phone application visualizing the evolution and the variability in the speed of a rowing boat in real-time. The application supports the rower in optimizing his/her movements to maximize the speed of the rowing boat and to optimize the uniformity of the speed of the rowing boat. The graphical user interface is kept simple in design so that the rower is not distracted due to the readout of the application data during the rowing. The accumulated acceleration data can be examined on a web interface after rowing.